Understanding Organizational Wage Structures: A Resource Dependence Approach - Pfeffer, Jeffrey; Davis‐Blake, Alison (Academy of Management Journal, 1987)
Data on the salaries for high level administrative positions in 608 colleges and universities were used to examine the relative salaries for six positions. Controlling for other factors, we found that the incumbents of positions that were more important in private institutions than in public ones were paid comparatively more in private than in public settings. Incumbents of positions that were more important in public institutions received comparatively more pay in those places. The results suggest that the criticality of a position, a factor that varies across work contexts, can help account for variation in wage structures across organizations.